2020
DOI: 10.1155/2020/6813405
|View full text |Cite
|
Sign up to set email alerts
|

Wheel and Deal in the Mitochondrial Inner Membranes: The Tale of Cytochromecand Cardiolipin

Abstract: Cardiolipin oxidation and degradation by different factors under severe cell stress serve as a trigger for genetically encoded cell death programs. In this context, the interplay between cardiolipin and another mitochondrial factor—cytochrome c—is a key process in the early stages of apoptosis, and it is a matter of intense research. Cytochrome c interacts with lipid membranes by electrostatic interactions, hydrogen bonds, and hydrophobic effects. Experimental conditions (including pH, lipid composition, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 226 publications
(360 reference statements)
0
45
0
Order By: Relevance
“…[1][2][3][4][5][6][7] The solution properties and binding events affect the heme environment and axial ligation, 1,[3][4][5][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] modifying the physiological role in vivo and the reactivity in vitro. 1,5,9,[13][14][15][16]18,19,[28][29][30][31][32][33][34][35][36][37][38][39]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] The solution properties and binding events affect the heme environment and axial ligation, 1,[3][4][5][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] modifying the physiological role in vivo and the reactivity in vitro. 1,5,9,[13][14][15][16]18,19,[28][29][30][31][32][33][34][35][36][37][38][39]…”
Section: Introductionmentioning
confidence: 99%
“…1,5,9,[13][14][15][16]18,19,[28][29][30][31][32][33][34][35][36][37][38][39][40] Indeed, cytochrome c has proven to be a multi-tasking protein whose biological role is modulated by external stimuli and cell conditions. 1,4,28,30,41 The paradigm of this tunable functionality in vivo is the interaction with cardiolipin (CL), a negatively charged glycerophospholipid found in the inner mitochondrial membrane (IMM), 30,40,42 which induces the cleavage of the Fe-S(Met80) bond, 1,5,9,19,21,28,30,32,39, imparting to cytc significant (lipo)peroxidase activity, which is crucial in triggering the apoptosis cascade. 1,5,28,30,40,47,73 In vitro, analogous heme axial ligand swapping from His/Met to His/His occurs upon chemical denaturation of both solution…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further experimental NMR relaxation measurements and hydrogen–deuterium exchange experiments on the Y48 p CMF variant revealed that the structure of the ncAA mutant exhibits enhanced dynamics around the p CMF-containing loop (also observed in MD simulations), which could explain the changes observed in its functionality ( Table 4 ). Upon cardiolipin binding, C c undergoes conformational changes which allows H 2 O 2 to access the heme crevice [157] . In the absence of cardiolipin, Y48 p CMF C c displayed higher peroxidase activity compared to the Y48E phosphomimetic variant.…”
Section: Resultsmentioning
confidence: 99%
“…Cytochrome c (cyt c) resides in the inner mitochondrial membrane (IMM) where it is bound to cardiolipin, an organelle-specific, negatively-charged phospholipid (20). Under physiological cell conditions, cyt c transfers electrons between complex III and IV of the electron transport chain and oxidizes superoxide anions to molecular oxygen (O2) as a ROS scavenger.…”
Section: Introductionmentioning
confidence: 99%